Two new species of Anaglyptus Mulsant from China (Coleoptera: Cerambycidae: Cerambycinae: Anaglyptini) - Wang, Yingqi; Zhao, Weiwei; Xie, Guanglin (Zootaxa, 2021)
Two new Anaglyptus species, Anaglyptus mucheni sp. nov. and Anaglyptus zhangjunqii sp. nov., are described and illustrated from China.